Síndrome de Burnout y procesos migrañosos en internos rotativos de medicina del Hospital Isidro Ayora de Loja - Guerrero Valdivieso, Gladys Roxana (2021)
The Burnout Syndrome (BS), also known as the emotional exhaustion syndrome, in which the alteration of the emotional state, the intellectual capacity and the physical state are added, these three work in a hierarchical way in a so-called vicious circle, for which a stress trigger is attributed, having as its cause overwork or job dissatisfaction, which leads to the development of this syndrome. (Lachiner Saborío Morales, Luis Fernando Hidalgo Murillo, 2015). Migraine is one of the pathologies that accompanies this syndrome the most, when established, it affects the activities that a professional usually performs, studies indicate that these two patterns are closely related. The BS can be triggered on any professional, and in different fields of work.There are several studies that indicate that health professionals, especially doctors and nurses, are more likely to develop this syndrome. It is known that there is a chance of developing the BS from the Internship year (IR) onwards, which corresponds to the pre-professional practices that every doctor who aspires to a professional degree must comply with. Being this a social interest, analytical, prospective and descriptive study with a sample of 84 interns from the “Hospital General Isidro Ayora” from Loja City, who correspond to the period between 2018 - 2019, and belong to the following universities: “Universidad Nacional de Loja” and “Universidad Técnica Particular de Loja”, the data was extracted directly by applying the Burnout Test, designated as the data collection instrument for this study, to each participant, obtaining the following results: a high incidence of emotional fatigue with a 60% (n = 50), as well as a high depersonalization of 82% (n = 69), in personal fulfillment with a low value of 79% (n = 66), therefore fulfilling the parameters for the diagnosis of the Burnout Syndrome in more than half of the Rotating Interns of medicine with 69% (n = 58) positive for the diagnosis on its totality, in addition to the migraine processes of these with a general positive value of 52% (n = 44). Keywords: migraine, headache, burnout, stress.